Relationships of Serum Iron Parameters and Hemoglobin with Forced Expiratory Volume in 1 Second in Patients with Chronic Obstructive Pulmonary Disease - Kim, Mi-Hye; Kim, Yong-Hwan; Lee, Duk-Chul (Korean journal of family medicine, 2018)
Although chronic obstructive pulmonary disease is a known cause of secondary polycythemia with elevated erythropoietic demands in response to hypoxemia, anemia is relatively common in patients with chronic obstructive pulmonary disease and is related to increased mortality. However, little is currently known about the relationship between various iron parameters and disease severity in chronic obstructive pulmonary disease patients. Data from the fifth Korean National Health and Nutrition Examination Survey, a population-based epidemiologic survey conducted in 2010-2012, were used. A total of 1,129 patients with chronic obstructive pulmonary disease were examined to reveal the associations between the forced expiratory volume in 1 second (FEV1) and hemoglobin and iron parameters, including serum iron, ferritin, total iron binding capacity, and transferrin saturation, using Spearman correlations and multiple linear regression analyses. The FEV1 was positively correlated with serum hemoglobin (γ=0.37, P<0.001), iron (γ=0.20, P<0.001), transferrin saturation (γ=0.19, P<0.001), and ferritin (γ=0.22, P<0.001), and negatively correlated with age (γ=-0.40, P<0.001) and lower in female patients (γ=-0.56, P<0.001) in the Spearman correlation. The FEV1 was independently associated with serum iron (β=0.049, P=0.035) and transferrin saturation (β=0.049, P=0.035) after adjusting for age, sex, and body mass index in the multiple linear regression analyses. The serum iron and transferrin saturation levels were independently associated with FEV1 as a marker of chronic obstructive pulmonary disease severity.